2020
DOI: 10.1111/cid.12903
|View full text |Cite
|
Sign up to set email alerts
|

The influence of submerged healing abutment or subcrestal implant placement on soft tissue thickness and crestal bone stability. A 2‐year randomized clinical trial

Abstract: PurposeAims of the study were: (a) to register crestal bone loss around 1.5 mm subcrestally placed implants and epicrestally placed implants with soft tissue tenting technique, (b) to record bone remodeling in subcrestal group, and (c) to determine the increase of vertical soft tissues after tenting.Materials and methodsThirty‐two patients with vertically thin tissues of 2 mm or less received 40 submerged bone level platform‐switched implants, divided into two groups—(a) 1.5 mm subcrestally placed implants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 17 publications
5
66
1
2
Order By: Relevance
“…It can be summarized that, during the one-stage approach while using a 2-mm healing abutment, we can achieve subcrestal implant position and augment STH. 28,29 Furthermore, during the second surgery of implant disclosure, there is no need to reflect a full-thickness flap, especially when it is generally accepted that elevation of a periosteal flap is directly correlated with the risk of crestal bone loss. 30,31 A short incision is sufficient to replace the 2 mm healing abutment with another abutment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be summarized that, during the one-stage approach while using a 2-mm healing abutment, we can achieve subcrestal implant position and augment STH. 28,29 Furthermore, during the second surgery of implant disclosure, there is no need to reflect a full-thickness flap, especially when it is generally accepted that elevation of a periosteal flap is directly correlated with the risk of crestal bone loss. 30,31 A short incision is sufficient to replace the 2 mm healing abutment with another abutment .…”
Section: Discussionmentioning
confidence: 99%
“…The use of 2 mm healing abutment shows various advantages in comparison with a cover screw. It can be summarized that, during the one‐stage approach while using a 2‐mm healing abutment, we can achieve subcrestal implant position and augment STH 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial tried to overcome the initial bone remodeling due to biologic width re-establishment by using a soft tissue tenting technique [ 23 ]. These implants were placed equicrestal with soft tissue tenting over 2 mm healing abutments.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies evaluating bone remodeling, rather than marginal bone loss, showed that implants placed subcrestally observed a greater extent of bone resorption during the first 12 month after prosthetic delivery [ 24 , 38 ]. Moreover, some clinical trials suggest that, in presence of thin supracrestal tissue, a subcrestal implant placement may reduce the probability for the implant to become exposed over time [ 39 , 40 , 41 ]. From the findings of the present study, it can be observed that at t 1 , the implant neck was located coronal to the marginal bone level only in very few cases.…”
Section: Discussionmentioning
confidence: 99%